Boston : a chronological & documentary history, 1602-1970 - Lankevich, George J. (Dobbs Ferry, N.Y. : Oceana Publications, 1974)
A chronology of important events in Boston's history accompanied by pertinent documents.
Include bibliography and index.
Keywords: Boston (Mass.) -- History -- Chronology; Boston (Mass.) -- History -- Sources; Boston (Mass.) -- History